OMG! My newborn baby has teeth! - Jamani, Nurjasmine Aida; Harun, Nor Asilah (The Malaysian Medical Gazette, 2017)
Julia had just given birth to a beautiful baby boy. She is so excited and started to breastfeed him. Her son could latch very well but each time Julia nursed her baby, she will purse her lips in pain. When she checked her baby’s mouth, she noticed that her newborn baby has a tooth at his lower gum! Could this be the source of pain to her while breastfeeding? What should Julia do?